Entrepreneurial Intentions: Analyzing Sociocultural and Perceptual Influences Using the Theory of Planned Behavior - Tripopsakul, Suchart (International Review of Management and Marketing, 2025)
This study examines how sociocultural and perceptual factors influence entrepreneurial intentions using the Theory of Planned Behavior (TPB). Based on 2,000 samples of Thai people aged between 18 and 64 years old from the Global Entrepreneurship Monitor (GEM) data in 2024, the study included a wide range of socio-cultural and perceptual factors related to entrepreneurship. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to verify the proposed hypotheses about the factors influencing entrepreneurial intention. The result revealed that opportunity recognition, a desirable career choice, a high level of successful entrepreneurs’ status, and self-confidence in their skills positively influence entrepreneurial intention. On the other hand, fear of failure negatively affects entrepreneurial intention. The results of the multi-group analysis show notable variations in the influence of fear of failure on entrepreneurial ambition among various demographic groups, particularly between genders and educational levels. This study enhances comprehension of how different circumstances and demographic traits influence entrepreneurial goals, offering significant insights for policymakers and educators seeking to promote entrepreneurial engagement.